2013
DOI: 10.1007/s00705-013-1743-2
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type rabies virus phosphoprotein is associated with viral sensitivity to type I interferon treatment

Abstract: Rabies virus (RABV) is a single-stranded, negative-sense RNA virus that causes a fatal neurological disease in humans and animals. Our previous studies have shown that lab-adapted, but not wild-type (wt), RABV enhances innate immune responses including type I interferon (IFN) and chemokines. To determine if treatment with type I IFN can inhibit RABV infection, mouse neuroblastoma and baby hamster kidney cells were treated with IFN-α before being infected with lab-adapted or wt RABV. It was found that lab-adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…Alongside this, stimulation of an innate immune response to infection also seems comparable in both natural and experimental infection suggesting that regardless of exposure route, innate cell markers are activated in a conserved manner [45]. This latter feature corroborates with molecular experimentation investigating mechanisms of immune avoidance by the lyssaviruses as a genus [46,47,48,49]. …”
Section: Transmission and Maintenancesupporting
confidence: 61%
“…Alongside this, stimulation of an innate immune response to infection also seems comparable in both natural and experimental infection suggesting that regardless of exposure route, innate cell markers are activated in a conserved manner [45]. This latter feature corroborates with molecular experimentation investigating mechanisms of immune avoidance by the lyssaviruses as a genus [46,47,48,49]. …”
Section: Transmission and Maintenancesupporting
confidence: 61%
“…In general, RABV street strains are more pathogenic than fixed viruses when inoculated via peripheral sites, and it is considered that evasion of innate immunity at peripheral sites (such as skin and muscles) is responsible for their high invasion into neurons from peripheral sites (Dietzschold et al, 2008). Moreover, a recent study showed that a street RABV strain (DRV strain) is more sensitive to IFN treatment than a laboratory-adapted fixed strain (B2C strain) and it was suggested that while street RABV strains are more sensitive to IFN treatment than laboratory-adapted RABV, they can strongly suppress IFN induction in host cells (Niu et al, 2013). Thus, the ability of the P protein to inhibit IKKe-mediated signalling may contribute to the strong interference with IFN induction by street viruses.…”
Section: Rabies Virus P Targets To Ikkementioning
confidence: 99%
“…DRV-Mexico is a wt RABV isolated from a rabid dog in Mexico in the 1990s (34). Recombinant CVSB2c expressing G [B2c(DRV-G)] or P [B2c(DRV-P)] from DRV-Mexico was constructed as described previously (35,36). Virus stocks were prepared in 1-day-old suckling mice as described previously (37).…”
mentioning
confidence: 99%